The mitochondrial genome of the Carniolan honey bee, Apis mellifera carnica (Insecta: Hymenoptera: Apidae) - Boardman, Leigh (Mitochondrial DNA B Resour, 2019)
Sequencing the mitochondrial genome of the Carniolan honey bee, Apis mellifera carnica, revealed 16,358 bp, consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. Phylogenetic analysis supported a close relationship to another south-eastern European (C-lineage) honey bee, A. m. ligustica.